(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
For all 2(nd+1) primitive idempotences in the ring, explicit terminology , where p and l are so different, peculiar primes A whole, obtained. An integer. Often discussed are the minimum width, polynomials and size generated by these primitive idempotents of the minimal cyclic codes. For eg, the minimum cyclic codes duration 22 parameters are discussed.